Disfungsi Keluarga Dalam Era Digital: Upaya Membangun Keluarga Kristen Yang Harmonis Di Era Digital - Sariyanto, Sariyanto (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This research focuses on the increasing dysfunction of families in the digital era, which exacerbates issues such as poor communication, prolonged conflicts, and the inability to resolve problems. The digital era aggravates the decline in family relations, adds pressure, and increases the risk of divorce due to various economic, communication, and lifestyle issues. The research questions include the causes of family dysfunction in the digital era, its implications for marital relationships, and the importance of faith in family life. This study uses a qualitative method and a literature review approach to explore the causes and implications of family dysfunction through literature from various sources. The conclusion of the research emphasizes that marriage is a sacred social and spiritual bond, fundamental to the continuity of Christian families. A functional family is achieved when spouses have mature thinking and spiritual maturity, fulfill family responsibilities, and prioritize God's love. Practical recommendations for addressing family dysfunction include improving communication between partners, understanding and applying spiritual values in daily life, and emphasizing Christian faith and spiritual principles in marriage to build a functional family.